Microbicidal potential of mercaptopropionic acid-capped cadmium telluride quantum dots against bacteria at varying reflux times - Ekwujuru, Ezinne U.; Klink, Michael J.; Monapathi, Mzimkhulu E (Edelweiss Applied Science and Technology, 2026)
Antimicrobial resistance to conventional antibiotics remains a critical global problem, necessitating the development of alternative therapeutic agents such as cadmium telluride quantum dots (CdTe QDs), which exhibit diverse biocidal activity due to their nanoscale dimensions and enhanced free radical generation. This study focused on the synthesis, characterization, and evaluation of the antimicrobial activity of mercaptopropionic acid-capped CdTe QDs (mCdTe QDs) at varying reflux times (1, 2, and 3 hours). The QDs were synthesized using a colloidal chemistry approach. Characterization was performed using Transmission Electron Microscopy (TEM), Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), and Energy-Dispersive X-ray (EDX). Antimicrobial activity was assessed using agar well diffusion, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) assays against Escherichia coli and Staphylococcus aureus. XRD analysis confirmed the hexagonal crystalline structure of the QDs, while SEM and TEM revealed uniform particles with average sizes of 3.029 nm, 2.656 nm, and 5.002 nm for 1-hour, 2-hour, and 3-hour reflux durations, respectively. A dose-dependent antimicrobial response was observed, with the 2-hour refluxed sample showing the highest bactericidal activity. Overall, mCdTe QDs exhibited higher efficacy against E. coli than S. aureus, highlighting their potential as effective antimicrobial agents.